Concepções e práticas de professores do ensino fundamental sobre o ensino de frações : um estudo em escolas de Cuiabá - Silva, Maria do Socorro Lucinio da Cruz (2013)
This paper deals with a study that aims to investigate and understand that concepts and practices that elementary school teachers are revealed in studies of fractions. In attempt to contribute to the production of existing knowledge, the relevance of this research reveals, above all, by finding ways to report in a more illuminating how is the teaching of fractions in elementary school. For this, we consider important and guiding our work, the following question: What conceptions and practices about teaching and learning fractions, are revealed by teachers working in elementary school? First, we performed a bibliographic study to indicate the theoretical aspects, related to fractions, beginning with a brief historical account of its rise and continuing with the discussion of the development of the concept of fractions students in the first years of elementary school. Thus, we elected to contribute to this study the following authors: BERLINGHOFF & GOUVÊA (2010), IMENES & LELLIS (1999), Caraga (1951), Ifrah (1989), GUMIERO (2002), BOYER (1974), LIMA (1994 ), & PIAGET Szeminska (1981), BRAZIL (1997/1998). Regarding the concepts and practices of teachers, used to enrich our reflections theorists: FIORENTINI (1995), Micotti (1999), PALM (1999), Medeiros (2005), BRIDGE (1992), Ribeiro (2007), Almeida (2006 ), Silva (2008), Darsie (1996/1999), Brunelli (2012), GARNICA (2008), TARDIF (2012), SHULMAN (2005) and SCHÖN (1995). The research was developed from a qualitative interpretive character, based on Bogdan & Biklen, (1994), Ludke & ANDRÉ (1986), FIORENTINI & Lorenzato (2006) and ALVES-MAZZOTTI & GEWANDSZNAJDER (2004). Our subjects are six teachers who work in schools of the state of education in Cuiabá and project participants Observatory of Education with a focus in Mathematics and Science Initiation. As instruments for data collection, use questionnaires, document analysis, classroom observation and interviews. In response to the problems of this investigation, we conclude that the concepts disclosed in the statements of teachers pass the traditional perspectives and constructivist teaching, but there is a greater tendency to constructivist model, and concepts revealed in the practices of the teachers have a strong tendency to the traditional perspective, except for one teacher who presents characteristics of constructivist model.